Delayed recognition of bilateral ureteral injury after gyneacological surgery - Mensah, J.E.; Klufio, G.O.; Ahiaku, F.; Osafo, C.; Gepi-Attee, S. (My University, 2008)
Background Iatrogenic bilateral ureteric injury is a rare complication of pelvic surgery, which if not recognised immediately results in significant morbidity and even mortality Objective To describe the presentation, aetiology and treatment of iatrogenic bilateral ureteric injuries recognised late following gynaecological surgery. Methods The case notes of 14 consecutive cases of bilateral ureteric injury managed between October 2000 and January 2007 were studied. Results Thirteen cases resulted from abdominal hysterectomy and one from vaginal repair of vesicovaginal fistula. Excessive bleeding with difficult haemostasis was the predominant predisposing factor. The indication for referral included oliguria, anuria, and urinary ascites or azotaemia. The time interval between the original surgery and the recognition of the injury ranged between 1 and 92 days. Patients in whom deterioration in renal function was ascribed to obstructive uropathy from bilateral ligation (postrenal renal failure) were referred much earlier than those in whom a diagnosis of prerenal renal failure was made (mean of 2 vs. 10 days). Five patients (36%) required dialyses before repair. All the repairs were done at open surgery. Thirteen survived with no loss of kidney. One patient died of overwhelming sepsis. Conclusions Late recognition and referral of bilateral ureteric injury was associated with serious complications. Post operative deterioration in a patient's renal function following pelvic surgery should be assumed to be due to ureteric obstruction until proven otherwise. Such patients should be promptly referred to centres with the facility for further investigation and management. Early open repair for these injuries is advocated.
Keywords: ureteral injury, renal failure, gynaecological surgery, anuria, hydronephrosis